1994
DOI: 10.2307/281935
|View full text |Cite
|
Sign up to set email alerts
|

Use Wear on Bone and Antler Tools from the Mackenzie Delta, Northwest Territories

Abstract: A series of experiments making and using bone and antler tools show that functional identifications of these tools can be made with confidence in some circumstances. Using principles from the field of tribology, the experiments demonstrate that different uses leave different microscopic traces on bone and antler. They also show that when the materials used are similar, the wear produced will be similar. In particular, wet materials, including snow, ice, wet hide, and wet antler all produce nearly identical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 14 publications
1
43
0
2
Order By: Relevance
“…Such studies include among others, the work of Anderson et al [6], who used tribological techniques to analyse micro-wear traces observed on flint blades for threshing grain and cutting straw from sites in the Near East from the later Neolithic to the Early Bronze Age. Similarly Le Moine's study of bone and antler tools [7] was carried out to demonstrate that distinctive patterns of wear on tool working faces depend on the activities tool were used for. For example bone and antler tools used to cut ice often show very different patterns of wear on the tool face compared with those used to cut wood.…”
Section: Tribology and Archaeologymentioning
confidence: 99%
“…Such studies include among others, the work of Anderson et al [6], who used tribological techniques to analyse micro-wear traces observed on flint blades for threshing grain and cutting straw from sites in the Near East from the later Neolithic to the Early Bronze Age. Similarly Le Moine's study of bone and antler tools [7] was carried out to demonstrate that distinctive patterns of wear on tool working faces depend on the activities tool were used for. For example bone and antler tools used to cut ice often show very different patterns of wear on the tool face compared with those used to cut wood.…”
Section: Tribology and Archaeologymentioning
confidence: 99%
“…En cambio, las de los instrumentos óseos utilizados para cortar o raspar piel, madera, corteza, etc. sí muestran rastros característicos de la materia trabajada (Semenov 1964;LeMoine 1997;Clemente et al 2002;Clemente y Gyria 2003;Maigrot 2003, entre otros). A los problemas mencionados hay que unir la falta de estudios experimentales relativos al uso de los arpones.…”
Section: Materiales Y Métodosunclassified
“…Oakes (1987:8 -10) lists the necessary tools as an ulu, a knife sharpener, a straight-edged scraper, a convex-edged scraper, and a scraping platform, commonly a board (Holtved, 1967:126). In the past, scapula and long-bone scrapers were used, and ground slate blades of uluit and scrapers were set into bone or wooden handles (Oakes, 1987;Lemoine, 1997). While bone scrapers are still in use today, ulu and scraper blades today are exclusively metal (Otak, 2005).…”
Section: Ethnographic Contextmentioning
confidence: 99%
“…However, the ulu was multi-purpose, and in other contexts had a bifacial edge (Rankin and Labrèche, 1991;Frink et al, 2003). Long bone and scapula scrapers were commonly used at this stage of the process (Boas, 1888;Birket-Smith, 1929, 1945Lemoine, 1997). The skin was laid on the woman's thigh or scraping board, and the scraping movements were made away from the body with the bevel of the ulu against the flesh side of the sealskin (Oakes, 1987;Issenman, 1997).…”
Section: Ethnographic Contextmentioning
confidence: 99%